2015
DOI: 10.1007/s10493-015-9963-7
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Amblyseius largoensis and Euseius alatus as biological control agent of Aceria guerreronis

Abstract: Amblyseius largoensis (Muma) (Acari: Phytoseiidae) and Euseius alatus De Leon (Acari: Phytoseiidae) are predatory mites that are mostly found on leaves and on the exposed fruit surface of coconut plants. Their morphology hampers the access to the microhabitat occupied by Aceria guerreronis Keifer (Acari: Eriophyidae), the most important pest of coconut fruits throughout the world. However, it was suggested that they can prey on A. guerreronis under natural conditions when this pest leaves its refuge to dispers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…The lack of reproductive isolation between the most morphometrically distant N. paspalivorus populations (RN and PB) supports the hypothesis that the studied populations belong to a single species, according to the biological concept of species (Mayr 1977). Previous studies have reported reproductive incompatibility among three geographically distant, N. paspalivorus populations (Benin, Ghana and Brazil) because of their association with different endosymbionts.…”
Section: Discussionsupporting
confidence: 81%
“…The lack of reproductive isolation between the most morphometrically distant N. paspalivorus populations (RN and PB) supports the hypothesis that the studied populations belong to a single species, according to the biological concept of species (Mayr 1977). Previous studies have reported reproductive incompatibility among three geographically distant, N. paspalivorus populations (Benin, Ghana and Brazil) because of their association with different endosymbionts.…”
Section: Discussionsupporting
confidence: 81%
“…Among these pests, there are many phytophagous mites (~10 species) that develop on the meristematic zone of the fruits, which is partly covered by the fruit perianth (Navia et al , 2005 a ; Lawson-Balagbo et al , 2008; Negloh et al , 2011). Under these perianths, the phytophagous mites are protected from pesticides and from many natural enemies, except for the smallest predatory mites (Lima et al , 2012; Monteiro et al , 2012; Melo et al , 2015; Da Silva et al , 2016). The feeding of the phytophagous mites on the meristematic zone of the fruits causes significant damage, with the fruit surface becoming necrotic, resulting in distorted coconuts and sometimes even in fruit abortion (Moore & Howard, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Over time, the distance between the perianth and the fruit surface becomes large enough to allow the entrance of some predator species (Lima et al , 2012). Several predatory mite species are frequently found associated with A. guerreronis on coconuts (Lawson-Balagbo et al , 2008; Reis et al , 2008; Negloh et al , 2011; Lima et al , 2012; Melo et al , 2015). Among them, Neoseiulus baraki (Athias-Henriot) (Acari: Phytoseiidae) is the most abundant predator, capable of developing and reproducing when feeding on coconut mites (Domingos et al , 2010; Melo et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The establishment of an effective analytical method that can identify egg remains from the phytoseiid gut will allow us to better evaluate predator-prey interactions between phytoseiid mites and spider mites, while also identifying the best predator. However, few such studies have examined the gut contents of phytoseiid mites (Melo et al, 2015;Rivera-Rivera et al, 2012;Wari et al, 2014). Therefore, in this study, I conducted laboratory feeding experiments in conjunction with fluorescent-labeled PCR to analyze the gut contents of phytoseiid mites.…”
Section: Introductionmentioning
confidence: 99%